2016
DOI: 10.1158/0008-5472.can-15-1883
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Controls an HDAC4-miR-206 Pathway of Oxidative Stress in Rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is an aggressive soft tissue cancer characterized by disturbed myogenic differentiation. Here we report a role for the oxidative stress response factor HO-1 in progression of RMS. We found that HO-1 was elevated and its effector target miR-206 decreased in RMS cell lines and clinical primary tumors of the more aggressive alveolar phenotype (aRMS). In embryonal RMS (eRMS), HO-1 expression was induced by Pax3/7-FoxO1, an aRMS hallmark oncogene, followed by a drop in miR-206 levels. Inhibit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 50 publications
(80 reference statements)
0
42
0
Order By: Relevance
“…However, no differences between cells of both genotypes were observed (Fig A). Since our recent studies revealed that HO‐1 can influence expression of miRNA molecules , the level of ESC‐specific miRNAs was further analyzed in Hmox1 +/+ and Hmox1 –/– iPSCs. Again, no differences in the expression of various miRNAs of miR‐290–295 cluster were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, no differences between cells of both genotypes were observed (Fig A). Since our recent studies revealed that HO‐1 can influence expression of miRNA molecules , the level of ESC‐specific miRNAs was further analyzed in Hmox1 +/+ and Hmox1 –/– iPSCs. Again, no differences in the expression of various miRNAs of miR‐290–295 cluster were observed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to CUR, the structure of DMC lacks one methoxy group directly linked to the benzene ring, as shown in Figure 1A. To investigate the pharmacological potential of DMC against OSCC, we examined short-term (24 h) and long-term treatment (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days) effects of DMC on the cell growth of primary SCC-9 and metastatic HSC-3 OSCC cells, respectively using thiazolyl blue tetrazolium bromide (MTT) and colony formation assays. As shown in Figure 1B, after 24 h, DMC treatment concentration dependently inhibited the cell proliferation of both OSCC cells, and the 50% growth inhibitory concentration (IC50) was around 50 µM.…”
Section: Dmc Exerts Antiproliferative Activity and Causes G2/m Cell Cmentioning
confidence: 99%
“…HO-1 was reported to be overexpressed or downregulated in different cancer types and has a multifaceted role in cancer development through regulating apoptosis, angiogenesis, and metastasis [11]. For example, the overexpression of HO-1 can enhance the proliferative or metastatic abilities of pancreatic cancer [12], melanomas [13], and rhabdomyosarcomas [14] in vitro and in vivo. In contrast, the overexpression of HO-1 exerts antiproliferative or anti-invasive abilities in breast, lung, and liver cancers [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-206 was downregulated in breast cancer, and suppressed cell proliferation by targeting cyclinD2 (13). Moreover, miR-206 also mediated cardiac hypotrophy (14) and oxidative stress (15). Study has proved that miR-206 mediated in the osteogenic differentiation in steroid-induced avascular necrosis of femoral head.…”
Section: Introductionmentioning
confidence: 98%